Thermal history and exhumation of basement rocks from Mesozoic to Cenozoic subduction cycles, central North Island, New Zealand. Issue 10 (13th October 2014) - Jiao, Ruohong; Seward, Diane; Little, Timothy A.; Kohn, Barry P.
Abstract A new thermochronological study of the basement rocks of the central North Island, New Zealand, records thermal and exhumation histories related to two subduction cycles since the latest Jurassic. The basement comprises metasedimentary terranes accreted onto eastern Gondwana during Mesozoic subduction. Since the Oligocene, these terranes have been located on the hanging wall of the Hikurangi subduction margin, overriding the Pacific Plate. Results of zircon fission track (121–264 Ma) analysis yield detrital or slightly reset ages; apatite fission track (19.8–122 Ma) and (U‐Th‐Sm)/He (10.3–95.2 Ma) ages are fully reset. Results from inverse thermal history modeling of the data of individual and stacked samples imply the following: (1) after their accretion, the basement rocks were cooled and exhumed to shallow depths of the crust in the Early Cretaceous (by 150–135 Ma). This was followed by an episode of reheating until 100 Ma, which we interpret to be the result of burial by sedimentation above the accretionary wedge during extensional deformation caused by continued underplating and thickening of the wedge from beneath. (2) From 100 Ma, our data indicate thermotectonic quiescence until the Oligocene ( 27 Ma). (3) During initiation of the Hikurangi Margin, the fore‐arc proto‐Axial Ranges began to exhume during the late Oligocene to early Miocene ( 27–20 Ma). Subduction‐triggered unroofing removed 1.2–2.8 km of overburden, most of which was probably the less lithified passive margin sediments. (4) Along the western central North Island, the exhumational response to the Hikurangi subduction was limited, with a total magnitude of erosion <1.5 km in the Cenozoic.